Physiological and Proteomic Analyses Indicate Delayed Sowing Improves Photosynthetic Capacity in Wheat Flag Leaves Under Heat Stress - Fei, Liwei; Chu, Jinpeng; Zhang, Xiu; Dong, Shuxin; Dai, Xinglong; He, Mingrong (Frontiers in Plant Science, 2022)
Background and aims Climate warming has become an indisputable fact, and wheat is among the most heat-sensitive cereal crops. Heat stress during grain filling threatens global wheat production and food security. Here, we analyzed the physiological and proteomic changes by delayed sowing on the photosynthetic capacity of winter wheat leaves under heat stress. Our aim is to provide a new cultivation way for the heat stress resistance in wheat. Methods Through 2 years field experiment and an open warming simulation system, we compared the changes in wheat grain weight, yield, photosynthetic rate, and chlorophyll fluorescence parameters under heat stress at late grain–filling stage during normal sowing and delayed sowing. At the same time, based on the iTRAQ proteomics, we compared the changes of differentially expressed proteins (DEPs) during the two sowing periods under high temperature stress. Key results In our study, compared with normal sowing, delayed sowing resulted in a significantly higher photosynthetic rate during the grain-filling stage under heat stress, as well as significantly increased grain weight and yield at maturity. The chlorophyll a fluorescence transient (OJIP) analysis showed that delayed sowing significantly reduced the J-step and I-step. Moreover, OJIP parameters, including RC/CSm, TRo/CSm, ETo/CSm, DIo/CSm and ΦPo, ψo, ΦEo, were significantly increased; DIo/CSm and ΦDo, were significantly reduced. GO biological process and KEGG pathway enrichment analyses showed that, among DEPs, proteins involved in photosynthetic electron transport were significantly increased and among photosynthetic metabolic pathways, we have observed upregulated proteins, such as PsbH, PsbR, and PetB. Conclusions Physiological and proteomic analyses indicate delaying the sowing date of winter wheat reduced heat dissipation by enhancing the scavenging capacity of reactive oxygen species (ROS) in flag leaves, and ensuring energy transmission along the photosynthetic electron transport chain; this increased the distribution ratio of available energy in photochemical reactions and maintained a high photosynthetic system assimilation capacity, which supported a high photosynthetic rate. Hence, delayed sowing may represent a new cultivation strategy for promoting heat stress tolerance in winter wheat.